ETIKA BISNIS PADA PENJUALAN DENGAN SISTEM OBRAL DI TOKO SEPATU: (Studi Kasus Toko Sepatu Arya Wringinanom, Gresik) - Putri Diana Sari; Hendra Dwi Prasetyo (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
This research is motivated by the complexity of sales strategies used by merchants to attract consumer attention, with one of them involving the implementation of a "sale" system. In the general paradigm, the term "sale" is often associated with offering relatively affordable prices; however, it should be noted that the concept of "sale" in the context of this research includes multifaceted considerations from sellers to categorize a product as a sale item. A qualitative field research method was chosen to explore in depth the location and dynamics of the sales event that became the focus of the research. The results show that the sales practice of implementing a sale system at Arya Shoe Shop has proven to be effective in attracting consumer interest. Nevertheless, it is unfortunate that this practice does not fully comply with the principles of business ethics, especially in the aspect of dishonesty. Recommendations are given for the improvement of business integrity by paying attention to ethical principles, particularly involving honesty, so that the success of the sales strategy is not only assessed in financial terms but also from the perspective of integrity and consumer trust.